2022
DOI: 10.1002/acn3.51499
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative changes in cognition and cerebrospinal fluid neurodegenerative disease biomarkers

Abstract: Objective Numerous investigators have theorized that postoperative changes in Alzheimer's disease neuropathology may underlie postoperative neurocognitive disorders. Thus, we determined the relationship between postoperative changes in cognition and cerebrospinal (CSF) tau, p‐tau‐181p, or Aβ levels after non‐cardiac, non‐neurologic surgery in older adults. Methods Participants underwent cognitive testing before and 6 weeks after surgery, and lumbar punctures before, 24 h after, and 6 weeks after surgery. Cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Consistent with previous study, the present study demonstrated that surgery and anesthesia-induced accumulation of hyperphosphorylated tau proteins was associated with cognitive impairment. However, a study by Berger et al failed to reveal the significant change of CSF tau, P-tau-181p, or Aβ levels before and after surgery in non-cardiac surgery [ 58 ]. This is contrary to our findings, which may be due to the various time points of assessment, the different definition of POCD, as well as the multiple types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous study, the present study demonstrated that surgery and anesthesia-induced accumulation of hyperphosphorylated tau proteins was associated with cognitive impairment. However, a study by Berger et al failed to reveal the significant change of CSF tau, P-tau-181p, or Aβ levels before and after surgery in non-cardiac surgery [ 58 ]. This is contrary to our findings, which may be due to the various time points of assessment, the different definition of POCD, as well as the multiple types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Samples and data were utilized from MADCO-PC (NCT01993836) 17 and INTUIT (NCT03273335) 18 studies. Markers of Alzheimer's Disease and neuroCognitive Outcomes after Perioperative Care (MADCO-PC) 17 was an observational cohort study that enrolled 140 older surgical patients (age ≥60) undergoing noncardiac, non-neurologic surgery.…”
Section: Methods: Study Informationmentioning
confidence: 99%
“…To date, most of the fluid biomarker studies in delirium and dementia have used cerebrospinal fluid (CSF) or blood (plasma or serum). Although CSF is thought to more accurately represent processes occurring in the brain, the collection of CSF, particularly in people with delirium, over multiple time points or in large-scale studies holds particular challenges [58][59][60][61][62] . Blood-based biomarkers are more accessible during acute illness, but plasma concentrations of biomarkers are often very low.…”
Section: Diagnosismentioning
confidence: 99%